Controllable design of multi-metallic aerogels as efficient electrocatalysts for methanol fuel cells. Issue 10 (20th February 2023) - Li, Lanqing; Gao, Wei; Ye, Jianqi; Fan, Haoxin; Wen, Dan
Abstract : A simple, general and steerable strategy to engineer nanotubular multi-component metallic aerogels is proposed. As-prepared PtNi nanotubular aerogels exhibited superb electrocatalytic properties towards both MOR and ORR for fuel cell applications. Abstract : Metallic aerogels with the hierarchical porous structure are promising materials for various electrocatalytic reactions; however, the regulation of their morphology and components remains a great challenge. Herein, three-dimensional porous PtNi aerogels composed of PtNi alloyed nanotubes with the tunable diameter and wall thickness were designed through a nanoengineering strategy of gelation and post treatment. The factors affecting the morphology and the mechanism for the growth of the multi-metallic aerogels were systematically investigated during their synthesis. Benefitting from the original interconnected networks and PtNi alloyed hollow blocks, the PtNi nanotubular aerogels displayed remarkable mass activity compared to the commercial Pt/C towards the oxygen reduction and methanol oxidation reactions for methanol fuel cells. Furthermore, different multi-component nanotubular aerogels of RuNi, Au–PtNi, and Ru–PtNi were also successfully fabricated using this nanoengineering strategy as active electrocatalysts. Therefore, the controllable nanoengineering strategy is considered a general pathway to obtain multi-metallic nanotubular aerogels, further providing a new idea for the design of hollow metallic aerogels as efficient electrocatalysts for fuel cell applications.